2018
DOI: 10.1016/j.ehj.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and microbial profile of central venous catheter related blood stream infection in medical cardiac care units, National Heart Institute, Egypt

Abstract: IntroductionCatheter related blood stream infection (CRBSI) is the main complication of central venous catheter (CVC) use. The aim of the study is to improve the safety of patients with central venous catheter in National Heart Institute (NHI) medical cardiac care units.MethodsA Prospective cohort study was conducted on one hundred and eleven cardiac patients in (NHI) cardiac care units from August 2017 to February 2018. All patients subjected to central venous catheter (CVC) in cardiac care units, NHI, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…The most common organisms in causing CLABSI were Acinetobacter (23.4%), S. aureus (13.1%), and Candida albicans (12.1%). It is consistent with a study which reported the incidence rate of CLABSI is 4.3%–26% of placed catheters and 0.46–30 per 1000 catheter days but lower than results from Alonso et al [10] and Khalil and Azqul et al [30] presenting the CLABSI rate of 12.6% and 9.9%, respectively, and higher than a report with 3.9% rate of CRBSI from Cheng et al who also reported S. aureus was the most common pathogens causing CLABIS [31]. However, a study carried out in China also found Acinetobacter baumannii (18.75%) was most common pathogen on intravascular catheters in ICU patients with catheter-related infection and followed by S. epidermidis [24].…”
Section: Discussionsupporting
confidence: 92%
“…The most common organisms in causing CLABSI were Acinetobacter (23.4%), S. aureus (13.1%), and Candida albicans (12.1%). It is consistent with a study which reported the incidence rate of CLABSI is 4.3%–26% of placed catheters and 0.46–30 per 1000 catheter days but lower than results from Alonso et al [10] and Khalil and Azqul et al [30] presenting the CLABSI rate of 12.6% and 9.9%, respectively, and higher than a report with 3.9% rate of CRBSI from Cheng et al who also reported S. aureus was the most common pathogens causing CLABIS [31]. However, a study carried out in China also found Acinetobacter baumannii (18.75%) was most common pathogen on intravascular catheters in ICU patients with catheter-related infection and followed by S. epidermidis [24].…”
Section: Discussionsupporting
confidence: 92%
“…The catheter lock solution is the injection of antimicrobials, wherein antibiofilms are instilled in the lumen of the CVC to eradicate organisms and prevent biofilm formation, thereby eliminating the source of CRBSI 9–11. At present, the most common lock solution is the use of heparin and saline to flush the lumen of the catheter 12…”
Section: Introductionmentioning
confidence: 99%
“…They found 11 (9.9%) cases of infection by the following agents: coagulase negative staphylococci , acinetobacter , Alcaligenes faecalis , enterobacter and klebsiella . The compliance of health workers to CVC care recommendations played a role in the presence of infections 3…”
mentioning
confidence: 99%
“…Particular attention should be given to unspecific clinical manifestations and the growing number of gram-negative bacteria which often pose diagnostic challenges and may potentiate the mortality rate 1,3,513,5. The two main concerns of such infections are the increasing mortality rate, which is up to 35%, and increasing hospital costs 6.…”
mentioning
confidence: 99%
See 1 more Smart Citation